The Effect of Constructive Play with Block Media on the Creativity of 5-6 Year Old Children - Hikma, Nur; Parwoto, Parwoto; Bachtiar, Muhammad Yusri (Jurnal Pendidikan Raudhatul Athfal, 2024)
This study aims to determine the effect of constructive play with block media on the creativity of children aged 5-6 years at Dharma Wanita Persatuan Kindergarten. The research approach used is a quantitative approach with the type of research Quasi Experiment Design with Non Equivalent Control Group Design research design. The population in this study amounted to 48 group B students at Dharma Wanita Persatuan Kindergarten. Sampling in this study was purposive sampling' The sample in this study was 16 children with 8 children as the experimental group and 8 children as the control group. Data collection techniques used are observation and checklist techniques. The data analysis technique used is descriptive statistics and non-parametric statistical analysis, namely the difference test (Wilcoxon signad rank test). Referring to the results of the study, there were changes in children's creativity seen from the average before and after being treated. From the results of the study it can be concluded that constructive play with block media has a significant influence on the creativity ability of children aged 5-6 years at Dharma Wanita Persatuan Kindergarten.